Strategies for Adapting a Higher Education Traditional Discipline on High-Performance Computer Architecture to Remote Learning - Pedrino, E. C.; Nicoletti, M. C. (International Journal of Computer Architecture Education, 2021)
This work reports the detailed process of adapting an undergraduate discipline about High-Performance Computer Architecture, traditionally face-to-face taught, to be taught in a remote mode. The discipline is part of the curricula of two Computer Science undergraduate courses. The adaptation was carried out to comply with precaution measures to avoid the dissemination of the covid-19 disease, caused by the new coronavirus. The article describes the reorganizational and methodological processes to adapt a face-to-face discipline into a remote mode, discusses ways to implement the guidelines established by the Department of Computing and presents the new structure adopted for theoretical and practical classes, as well as the results of the assessment of the new teaching approach adopted for dealing with the pandemic. The process of adapting a face-to-face discipline to a remote mode was quite successful, considering the short period of time the adaptation needed to be implemented, as well as the many decisions involved in the processes detailed in the paper. The teaching-learning process throughout the remote course was considered satisfactory by the students, with a 95% confidence interval.